NATMAP digital maps 1:100,000 scale topographic raster maps of Australia - Geoscience Australia (Canberra : Geoscience Australia, 2010)
"NATMAP Digital Maps contains Geoscience Australia's 1:100 000 scale topographic maps"--Back of container.
Title from container.
Geocat 68456.
Minimum system requirements: Windows 98/ME/2000/XP/Vista (Mac OS not supported) ; 333MHz Pentium II CPU or equivalent, 64MB RAM, 40MB free space ; 800x600 screen resolution with 64K colours ; Internet connection to download viewing software.
Digital content preserved
Keywords: Australia -- Maps; Topographic maps